Burst strength analysis of thin composite pressure vessels - Afrathim, A. (Elsevier Ltd, 2021)
This paper highlights the method to analyze the first ply failure (FPF) burst pressure of thin composite pressure vessels, using finite element (FE) software. Commercial FE software Autodesk Simulation Mechanical was employed for this purpose. The simulation results were validated with three case studies available in the literature. The Tsai-Wu and maximum stress failure criterions were used to identify the FPF burst pressure. Furthermore, the feasibility of basalt fibre reinforced composite for usage in pressure vessel application was investigated. The validated case study was re-simulated using basalt/epoxy, E-glass/epoxy, and S2 fibreglass/epoxy as the pressure vessel material. The simulation results indicated that the FPF burst pressure of composite pressure vessel using basalt/epoxy was marginally greater than S2 fibreglass/epoxy, and exceedingly greater than E-glass/epoxy. Â© 2021 Elsevier Ltd. All rights reserved.